Sistem Pengkondisian Otomatis Suhu Dan Kekeruhan Air Budidaya Ikan Patin Berbasis Internet of Things (IoT) - Lovinardo Devharo; n/a Rahmadwati; Ponco Siwindarto (Jurnal Mahasiswa TEUB, 2022)
Internet of Thing (IoT) is a concept where an object has the ability to transfer data over a network without requiring human-to-human or human-to-computer interaction. IoT really helps technological developments, especially in terms of monitoring. In this study, an IoT based automatic monitoring system for catfish that designed focus on the quality of its water. The variables that are controlled in this system are temperature and turbidity of water in the fish tank. Temperature control occurs when the temperature sensor detects a temperature lower than ideal temperature, then the system will turn on the heater until the temperature back to ideal. Water turbidity control occurs when the turbidity sensor detects that the water turbidity exceeds the normal limit, then the system will open the solenoid valve so that water will be discharged. The values of water temperature and turbidity will be displayed realtime on the LCD and Blynk.Keywords— catfish cultivation, internet of things, automatic, temperature, turbidity, monitoring